THE RELATIONSHIP BETWEEN HEALTH SERVICES AND BPJS HEALTH MEMBERSHIP IN THE PANDAN PUBLIC HEALTH CENTER WORK AREA, SINTANG REGENCY - Elvi Juliansyah; Ria Damayanti; Sunarti (CV. ADIBA AISHA AMIRA, 2026)
Background: The social health insurance system is based on the principle of solidarity between workers and employers, and guarantees access to healthcare services for the entire population. While coverage is high, the level of participant contribution activity still needs to be increased, with a target of at least 75% active participants. The aim: The purpose of this study is to explain the relationship between health services and BPJS Health membership in the Pandan Community Health Center Working Area, Sintang Regency, West Kalimantan. Method: The quantitative research method with a cross-sectional approach uses chi-square test analysis with a 95% confidence level and a 5% error rate, so the number of samples needed is around 100 respondents. The results: The results of the study showed that there was a relationship between health services (p value = 0.008 and OR = 5.179) and BPJS Health participation. Conclusion: there is a relationship between health services and BPJS health membership.